An Analysis of Lexical Cohesion Tools Used In International Research Abstracts and Local Research Abstract: (A Comparative Study) - Mohammed, Hajer; Amir, Asmaa (Tobruk University Journal of Social and Human Sciences, 2024)
This study investigates the utilization of lexical cohesion (LC) in research articles (RAs) by academic writers, as well as the types of LC employed, given that the effective use of LC enhances the coherence of academic writing. A total of thirty articles were selected from two journals in the field of theoretical linguistics, comprising fifteen articles from local Libyan journals and fifteen from a reputable international journal. The results of the analysis showed that local scholars used lexical cohesion tools more frequently than their international counterparts. Specifically, local scholars utilized synonymy, hyponymy, and meronomy more often, while international scholars relied on antonymy more frequently. Interestingly, both groups used collocation almost equally.